Relation between Activator Factors and Compliance Behavior of Using Personal Protective Equipment on Technician Workers at PT ARPS Surabaya - Mu'afiah Mu'afiah; M. Misbakhul Munir; Indriati Paskarini (Universitas Airlangga, 2021)
Introduction: Equipment that must be used by workers for work safety when working with potential work hazards or accidents is personal protective equipment (PPE). The purpose of this study was to analyze the factors associated with the use of PPE in the workforce of technicians at PT. APRS in terms of PPE usage. Methods: This research was an analytic observational study, with cross sectional design. The subjects of this study were all of the technician workforce in the section of Blow molding, Maintenance and Injection Molding unit, totalling 39 respondents. Results: This study showed that activator factors such as perception (r = 0.108), knowledge of occupational health and safety (r = -0.104), and PPE regulation (r = -0.166) had a weak relationship with safety behavior on compliance with PPE implementation. Conclusions: The workforce behaved poorly in using PPE in the workplace. In the Blow Molding, Maintenance and Injection Molding unit, workers who had a moderate level of perceptions, workers who had a moderate level of knowledge, and workers who had a enough ability to comply with PPE regulations.Keywords: knowledge, perception, personal protective equipment, policy